Functional Outcome of Latarjet procedure for Traumatic Anterior Shoulder Instability. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of open Latarjet procedure for traumatic recurrent anterior shoulder instability in young patients Methods: This descriptive study was conducted in Orthopedics and spine unit Hayatabad Medical Complex Peshawar from 25th January 2018 to 25th December 2021. All adults patients with traumatic recurrent anterior shoulder instability fulfilling the inclusion criteria were treated with open Latarjet Procedure. Functional outcome at two years was assessed with Rowe score and graded as excellent, good, fair and poor. The pre operative and post operative Rowe score was compared and P value calculated with paired sample t test. P value